Investigation of neutron and gamma radiation protective characteristics of synthesized quinoline derivatives - Aygun, Bunyamin; Alaylar, Burak; Turhan, Kadir; Sakar, Erdem; Karadayi, Mehmet; Abu Al-Sayyed, Ibrahim; Pelit, Emel; Gulluce, Medine; Karabulut, Abdulhalik; Turgut, Zuhal; Alim, Bunyamin (TAYLOR & FRANCIS LTD, 2020)
Purpose: Quinoline is formed by various natural compounds, such as alkaloids from the cinchona plant, which exhibit various biological activities, and is an important building material for the development of new drugs. Quinoline can be used in anti-radiation drug development but radiation interaction properties must be determined. Material and methods: In this study, six types of synthesized quinoline derivatives were used. Fast neutron removal cross-section, mean free path, half value layer and transmission number were theoretically determined by using GEometry ANd Tracking 4 and FLUktuierende KAskade simulation codes for neutron shielding. Neutron dose absorption rates were determined using the(241)Am-Be fast neutron source and the Canberra NP series portable BF(3)gas proportional neutron detector. Gamma radiation shielding parameters were determined by using WinXCom and PSY-X/PSD software. Additionally, the genotoxic potentials of the derivatives were assessed by using the Ames/Salmonellabacterial reversion assay. Results and conclusions: Neutron shielding parameters such as removal cross-section, mean free path, half value layer and transmission number were theoretically determined for fast neutrons. To determine neutron absorption capacity of quinoline derivatives, neutron absorption, experiments were conducted. In addition, gamma radiation shielding parameters were calculated such as the mean free path (MFP), mass attenuation coefficient (mu t), half value thickness layer (HVL) and effective atomic number (Zeff) in the energy range of 0.015-15 MeV. The results of the all quinoline derivatives have excellent fast neutron shielding power compared to ordinary concrete. In addition, all quinoline derivatives have been found to have the capacity to attenuate gamma radiation. Moreover, they absorb well in both types of radiation, do not cause secondary radiation, and they are genotoxically safe at the tested concentrations. This study has demonstrated that these products can be used as active ingredients for a drug to be developed against radiation.
Keywords: Drugs; genotoxicity; gamma; neutron; shielding; quinoline derivatives; DIELS-ALDER REACTIONS; PARAMETERS; REMOVAL; NUMBER; REGION; Life Sciences & Biomedicine - Other Topics; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging